2017
DOI: 10.1159/000458468
|View full text |Cite
|
Sign up to set email alerts
|

The U2 snDNA Is a Useful Marker for B Chromosome Detection and Frequency Estimation in the Grasshopper <b><i>Abracris flavolineata</i></b>

Abstract: In this study, we describe a strategy to determine the presence of B chromosomes in the living grasshopper Abracris flavolineata by FISH using U2 snDNA as a probe in interphase hemolymph nuclei. In individuals without B chromosomes, (0B) 2 dot signals were noticed, corresponding to A complement U2 snDNA clusters. In +1B and +2B individuals, 4 or 8 additional signals were noticed, respectively. In all cases, the absence or presence of 1 or 2 B chromosomes correlated in hemolymph and in somatic or germline tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A recent study has reported that circular RNA TMEM87A is localized in the cytoplasm of human gastric cancer cells BGC823 and MKN45 [22] . U2 snDNA has been shown to be localized in the nucleus [23] . On the basis of previous reports, we used circular RNA TMEM87A and U2 snDNA as controls.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has reported that circular RNA TMEM87A is localized in the cytoplasm of human gastric cancer cells BGC823 and MKN45 [22] . U2 snDNA has been shown to be localized in the nucleus [23] . On the basis of previous reports, we used circular RNA TMEM87A and U2 snDNA as controls.…”
Section: Resultsmentioning
confidence: 99%